Performance assessment and microstructural characterization of combined surface, chemical and polymer treated crumb rubber concrete - B. Kevin; Prabir K. Sarker; Mini K. Madhavan (Scientific Reports)
Abstract Discarded tire crumb rubber is considered as a sustainable alternative to natural aggregate in the production of concrete. However, this rubberized concrete usually exhibits lower performance attributes because of its low density, rigidity, and hydrophobic properties. Current study investigates the use of treated crumb rubber as a partial replacement for fine aggregate in M30 grade concrete. Various treatment methods such as chemical (NaOH), surface (cement coating), and combined treatments (NaOH + cement coating (CCOH), NaOH + cement + latex coating (CCOHLX)), were employed to enhance bonding of rubber in the matrix. Microstructural analysis using SEM and EDX revealed improved surface roughness and adhesion in treated crumb rubber. Compressive strength increased by 24.7% and 11.8% for 10% replacement, and 27% and 21.7% for 20% replacement, with CCOH and CCOHLX treatments, respectively. Durability tests showed 25.9% and 36.7% improvements in resistance to chloride penetration and reduced abrasion mass loss by 15% and 23.3% for CCOH-M and CCOHLX-M mixes. The SEM images showed a better adhesion of the CCOH and CCOHLX treated crumb rubbers. The study concludes that 20% replacement of aggregate with CCOH and CCOHLX treated crumb rubber optimizes strength and durability, thus offering an environmentally friendly solution for tire waste management.